Penerapan Model Pembelajaran Cooperative Learning untuk Meningkatkan Motivasi Belajar pada Mata Kuliah Kapita Selekta Pendidikan Mahasiswa FKIP UNISRI - Sugiaryo Sugiaryo; Sutoyo Sutoyo (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
Learning is a daily activity for students. there are also learning activities that do not include lecturer designs, because of the students' own desires. There are several motivational theories, among others: encouragement theory, intensive theory, achievement motivation theory, competency motivation theory, and motivation needs theory. cooperative learning system or cooperative learning is a teaching system that provides opportunities for fellow students to work together on structured tasks. Cooperative learning is known as group learning. This research is a Classroom Action Research (CAR) which can also be called development research. The study was conducted in 2 cycles, by applying methods in cooperative learning. Based on the discussion that has been done in the previous chapter, in general, it can be concluded that the application of STAD type cooperative learning methods can increase student motivation in the Capita Selekta Education Course. This was evidenced by the average student motivation in the high category in both Cycles I and Cycle II with a percentage of 56.25 and 62.50%. With an increase in student motivation significantly also affect the results of learning evaluations with a complete score category> 75.